Violence Against Women and Girls : Social Protection Brief - Gennari, Floriza; Arango, Diana; McCleary-Sills, Jennifer; Hidalgo, Nidia (World Bank, Washington, DC, 2015)
The definition of social protection (SP) programs varies widely, as do the types of interventions included and the specific outcomes sought. These programs can be implemented through public and/or private sectors, with the involvement of single or multiple government sectors, or by some combination of these actors. This brief will specifically focus on four types of social protection interventions: social assistance, social insurance, labor market programs, and early childhood development. It will offer suggestions for integrating violence against women and girls (VAWG) prevention efforts within these interventions. These areas of focus are meant to be illustrative of different social protection programs, rather than to reflect the full breadth of SP programs. In general, SP programs are public interventions that support the poorest populations and assist individuals, households, and communities to better overcome social and economic risks. Examples of programs include: a) social assistance (social safety nets): cash transfers, school feeding, and targeted food assistance; b) social insurance: old-age and disability pensions and unemployment insurance; c) labor market programs: skills-building programs, job-search and matching programs, and improved labor regulations; and d) early childhood development. Other program interventions, which fall under what is referred to as social protection, aim to strengthen families abilities to respond to hardships by promoting gender equality. Examples include early childhood development, projects that focus on at-risk youth, or targeted poverty alleviation programs.